1997
DOI: 10.1084/jem.186.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Experimental Autoimmune Encephalomyelitis with Genetically Modified Memory T Cells

Abstract: The migratory properties of memory T cells provide a model vector system for site-specific delivery of therapeutic transgene factors to autoimmune inflammatory lesions. Lymph node cells from (SWR×SJL)F1 mice immunized with the p139–151 determinant of myelin proteolipid protein (PLP) were transfected with a DNA construct that placed the anti-inflammatory cytokine interleukin-10 (IL-10) cDNA under control of an antigen-inducible IL-2 promoter region. Isolated T cell clones demonstrated antigen-inducible expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(84 citation statements)
references
References 28 publications
2
82
0
Order By: Relevance
“…Genetic modification of autoreactive T cells to express IL-10, 36,37 or local delivery of IL-4 by retrovirus-transduced T cells 38 can ameliorate experimental autoimmune disease in mice. Transfer of a variety of genes, including IL-1 receptor (R) antagonist, 39 Fas L, 40 soluble (s)IL-1R or tumor necrosis factor (TNF) ␣R 41 to the site of inflammation ameliorates experimental antigen-induced arthritis.…”
Section: Figure 7 Priming Of T Cells With Ctla4ig-transduced DC Reducmentioning
confidence: 99%
“…Genetic modification of autoreactive T cells to express IL-10, 36,37 or local delivery of IL-4 by retrovirus-transduced T cells 38 can ameliorate experimental autoimmune disease in mice. Transfer of a variety of genes, including IL-1 receptor (R) antagonist, 39 Fas L, 40 soluble (s)IL-1R or tumor necrosis factor (TNF) ␣R 41 to the site of inflammation ameliorates experimental antigen-induced arthritis.…”
Section: Figure 7 Priming Of T Cells With Ctla4ig-transduced DC Reducmentioning
confidence: 99%
“…[14][15][16][17][18] One approach has been to genetically modify antigen-specific T cells to deliver immunoregulatory molecules. [45][46][47][48][49] Direct injection of naked DNA encoding anti-inflammatory cytokines has also been the focus of a significant number of EAE studies. 14 Plasmids encoding the IL-4 gene together with myelin antigen, the PLP (139-151) epitope or myelin oligodendrocyte glycoprotein (MOG) have been shown to elicit either protection in the case of PLP or amelioration of established disease in the case of MOG.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%